2018
DOI: 10.1111/jnc.14558
|View full text |Cite
|
Sign up to set email alerts
|

DARPP‐32 in the orchestration of responses to positive natural stimuli

Abstract: Dopamine- and cAMP-regulated phosphoprotein (M 32 kDa, DARPP-32) is an integrator of multiple neuronal signals and plays a crucial role particularly in mediating the dopaminergic component of the systems involved in the evaluation of stimuli and the ensuing elaboration of complex behavioral responses (e.g., responses to reinforcers and stressors). Dopamine neurons can fire tonically or phasically in distinct timescales and in specific brain regions to code different behaviorally relevant information. Dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 164 publications
1
25
0
Order By: Relevance
“…More recently, Guilarte et al () showed that young adult non‐human primates chronically exposed to 15–20 mg/kg MnSO 4 per week via jugular catheter injection exhibited reduced DA release in the frontal cortex, relative to baseline controls, an observation not greatly different from the exposure‐dependent ordering found in the DA time course in our work. Interestingly, our findings may help explain the Mn‐induced effects of another protein involved in the catecholaminergic system, DARPP‐32, a DA‐regulated phosphoprotein that is known to play a role in DAergic protein kinase A‐dependent signaling (Scheggi, Montis, & De, ). Given that D1 receptor activation is known to stimulate phosphorylation of DARPP‐32 at threonine 34, and the fact that Cordova et al () recently reported that neonatal exposure to 20 mg Mn kg –1 day –1 i.p over PND 8–27 caused a decrease in DARPP‐32 phosphorylation at threonine 34, their finding may reflect the synaptic alterations between D1 and D2 receptor levels reported here.…”
Section: Discussionmentioning
confidence: 82%
“…More recently, Guilarte et al () showed that young adult non‐human primates chronically exposed to 15–20 mg/kg MnSO 4 per week via jugular catheter injection exhibited reduced DA release in the frontal cortex, relative to baseline controls, an observation not greatly different from the exposure‐dependent ordering found in the DA time course in our work. Interestingly, our findings may help explain the Mn‐induced effects of another protein involved in the catecholaminergic system, DARPP‐32, a DA‐regulated phosphoprotein that is known to play a role in DAergic protein kinase A‐dependent signaling (Scheggi, Montis, & De, ). Given that D1 receptor activation is known to stimulate phosphorylation of DARPP‐32 at threonine 34, and the fact that Cordova et al () recently reported that neonatal exposure to 20 mg Mn kg –1 day –1 i.p over PND 8–27 caused a decrease in DARPP‐32 phosphorylation at threonine 34, their finding may reflect the synaptic alterations between D1 and D2 receptor levels reported here.…”
Section: Discussionmentioning
confidence: 82%
“…Since protein phosphatases act in a wide range of cell types and are commonly associated with deactivation and ubiquitylation of proteins [13], Ppp1r1b encoding PP1 inhibitor subunit DARPP-32 was underlined as one of the rare neurospecific genes expressed at very high rates specifically in dorsal striatum MSNs and playing a crucial role in the 'orchestration' of neurotransmission [14]. Ppp1r1b is expressed in the upper bound of the expression range for dorsal striatum-related proteinencoding genes and is implicated as an ultimate factor of MSNs phosphorylation kinetics regulation [15]. It has been proven to be involved in many pathophysiological processes [16][17][18].…”
mentioning
confidence: 99%
“…Conversely, Cdk5, which is activated in D2-dopaminoceptive MSNs by Ca2 + provided by AMPA/NMDA receptors, phosphorylates DARPP-32 at Thr75, turning DARPP-32 into PKA inhibitor [23]. The pathway is being regularly updated, and published elsewhere [15]. Besides, MSNs express dorsal striatum specific Tyrosine phosphatase STEP (encoded by Ptpn5), which functions alternatively to serine/threonine phosphatases [24].…”
mentioning
confidence: 99%
“…In our experimental conditions appetitive motivational anhedonia is closely linked to reduced dopaminergic responses to sucrose, evaluated in terms of increases in extraneuronal dopamine levels in the NAcS of non food-deprived rats [35] . Indeed, modifications in dopamine D 1 receptor-dependent signaling in the NAcS after sucrose consumption, measured as PKA-dependent phosphorylation of Thr34 DARPP-32, positively correlate with changes reported in extraneuronal dopamine levels [ 35 , 46 , 47 ]. Repeated pharmacological treatments that counteract these blunted dopaminergic responses to a natural reinforcer reestablish the motivation to operate for a reward, as indicated by PR and BP values in sucrose self-administration [ 35 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%